Penggunaan Instrumen Test Three Tier Multiple Choice Untuk Mengidentifikasi Miskonsepsi Pada Konsep Fisika - Suhadi Suhadi; Mutiara Basima Atsilah (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
Physics is a science that has many different concepts. Many students have difficulty understanding concepts in physics learning. Because learning physics tends to interpret physics concepts based on formulas contained in textbooks without going through the process of discovery, processing, and development of knowledge can cause students not to master the concept properly. This can cause many students to experience misconceptions. Efforts and instruments are needed to measure student misconceptions which are commonly called three-tier multiple choice diagnostic tests. This study aims to provide a reference related to the identification of misconceptions in students using a three-tier multiple choice test instrument on physics concepts. the researcher conducted research using the meta-analysis method which is an effort to summarize various research results documenting some data related to the identification of misconceptions using a three tier multiple choice instrument which was published in a national journal. From this study it is proven that the use of a three tier multiple choice instrument can identify students' misconceptions.